Physical Activity and Sex Hormone Levels in Estradiol- and Placebo-Treated Postmenopausal Women - Choudhury, Farzana (2011)
OBJECTIVE: Postmenopausal changes in the hormonal milieu in women with or without hormone therapy (HT) are hypothesized to be the pathway for a number of menopause-associated modifications in physiology and disease risk. Physical activity may modify these changes in women’s hormone profiles. The crucial yet complex relationship between physical activity and physiologic and pharmacologic sex hormone levels in postmenopausal women has not been investigated sufficiently. METHODS: Using structured recall, physical activity was assessed longitudinally over two years in 194 postmenopausal women (90 randomized to daily 1 mg 17β-estradiol and 104 to placebo) in the Estrogen in the Prevention of Atherosclerosis Trial. Levels of physical activity were correlated to serum sex hormone and serum hormone-binding globulin (SHBG) levels in each treatment group. RESULTS: In placebo-treated women, total energy expenditure was positively associated with sex hormone-binding globulin (SHBG) (p<0.001) and inversely associated with testosterones (total, bioavailable, free) and androstenedione (p<0.001 for all), as well as with estradiol (p=0.02). In estradiol-treated women, estradiol levels were inversely associated with total energy expenditure (p=0.002) and weekly hours spent in moderate or more vigorous physical activity (p=0.001). CONCLUSION: Physical activity is associated with lower serum levels of estradiol in both HT-treated and untreated women. In placebo-treated women only, physical activity is associated with reduced androgen levels and elevated SHBG levels.